Structurally symmetric near-infrared fluorophore IRDye78-protein complex enables multimodal cancer imaging - Yang, Jiang (Theranostics, 2021)
Rationale: Most contemporary cancer therapeutic paradigms involve initial imaging as a treatment roadmap, followed by the active engagement of surgical operations. Current approved intraoperative contrast agents exemplified by indocyanine green (ICG) have a few drawbacks including the inability of pre-surgical localization. Alternative near-infrared (NIR) dyes including IRDye800cw are being explored in advanced clinical trials but often encounter low chemical yields and complex purifications owing to the asymmetric synthesis. A single contrast agent with ease of synthesis that works in multiple cancer types and simultaneously allows presurgical imaging, intraoperative deep-tissue three-dimensional visualization, and high-speed microscopic visualization of tumor margins via spatiotemporally complementary modalities would be beneficial. Methods: Due to the lack of commercial availability and the absence of detailed synthesis and characterization, we proposed a facile and scalable synthesis pathway for the symmetric NIR water-soluble heptamethine sulfoindocyanine IRDye78. The synthesis can be accomplished in four steps from commercially-available building blocks. Its symmetric resonant structure avoided asymmetric synthesis problems while still preserving the benefits of analogous IRDye800cw with commensurable optical properties. Next, we introduced a low-molecular-weight protein alpha-lactalbumin (α-LA) as the carrier that effectively modulates the hepatic clearance of IRDye78 into the preferred renal excretion pathway. We further implemented (89)Zr radiolabeling onto the protein scaffold for positron emission tomography (PET). The multimodal imaging capability of the fluorophore-protein complex was validated in breast cancer and glioblastoma. Results: The scalable synthesis resulted in high chemical yields, typically 95% yield in the final step of the chloro dye. Chemical structures of intermediates and the final fluorophore were confirmed. Asymmetric IRDye78 exhibited comparable optical features as symmetric IRDye800cw. Its well-balanced quantum yield affords concurrent dual fluorescence and optoacoustic contrast without self-quenching nor concentration-dependent absorption. The NHS ester functionality modulates efficient covalent coupling to reactive side-chain amines to the protein carrier, along with desferrioxamine (DFO) for stable radiolabeling of (89)Zr. The fluorophore-protein complex advantageously shifted the biodistribution and can be effectively cleared through the urinary pathway. The agent accumulates in tumors and enables triple-modal visualization in mouse xenograft models of both breast and brain cancers. Conclusion: This study described in detail a generalized strategic modulation of clearance routes towards the favorable renal clearance, via the introduction of α-LA. IRDye78 as a feasible alternative of IRDye800cw currently in clinical phases was proposed with a facile synthesis and fully characterized for the first time. This fluorophore-protein complex with stable radiolabeling should have great potential for clinical translation where it could enable an elegant workflow from preoperative planning to intraoperative deep tissue and high-resolution image-guided resection.